Pengaruh Penggunaan Media Powtoon Berbasis PBL terhadap Kemampuan Koneksi Matematis Siswa Sekolah dasar - Vega Kharisma; Elly’s Mersina Mursidik; Rissa Prima Kurniawati (Prosiding Konferensi Ilmiah Dasar, 2022)
This research is motivated by students who have difficulties in understanding the material, especially in mathematics and learning subjects that have not used the media. This study aims to determine the effect of using PBL-based powtoon media on the mathematical connection of elementary school students. This research uses quantitative research with Quasi Experimental Design research in the form of Posttest Only Control Design. Data collection techniques for this research are test and documentation. The research instrument used is the syllabus, lesson plans and tests. The data used are the results of posttest scores from the control class and the experimental class, then several tests are carried out, namely normality test, homogeneity test, and hypothesis testing. Based on the results of hypothesis testing, it can be concluded that there is an effect of using PBL-based powtoon media on the mathematical connection abilities of students at SDN 02 Pangongangan.